Manajemen Data Yang Efektif: Solusi Untuk Mencegah dan Mengatasi Duplikasi Data Dalam Perusahaan - Nazwa Hanifah; Muhammad Irwan Padli Nasution (Epsilon Journal of Management, 2025)
This study aims to analyze the causes of data duplication in companies, its impact on operational efficiency, and the solutions that can be implemented to prevent and address it. Using a qualitative method with a library research approach, this study examines various literature related to data management. The findings indicate that data duplication is caused by a lack of standardization, input errors, and weak integration systems. The recommended solutions include the implementation of database management technology, regular data audits, and strict data governance policies. With the right strategies, companies can enhance efficiency and ensure data accuracy in business decision-making.